2022
DOI: 10.1007/s10462-022-10188-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neuro-Fuzzy System application trends, challenges, and future perspectives: a systematic survey

Abstract: Deep neural networks (DNN) have remarkably progressed in applications involving large and complex datasets but have been criticized as a black-box. This downside has recently become a motivation for the research community to pursue the ideas of hybrid approaches, resulting in novel hybrid systems classified as deep neuro-fuzzy systems (DNFS). Studies regarding the implementation of DNFS have rapidly increased in the domains of computing, healthcare, transportation, and finance with high interpretability and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 135 publications
0
19
0
Order By: Relevance
“…The methodology used in this study was adopted based on the SLR guidelines [31], [32]. Additionally, this systematic study followed the reporting style and flow of comprehensive studies [33], [34]. The modified mapping process employed in this study is shown in Figure 1 and further explained in Section III-A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology used in this study was adopted based on the SLR guidelines [31], [32]. Additionally, this systematic study followed the reporting style and flow of comprehensive studies [33], [34]. The modified mapping process employed in this study is shown in Figure 1 and further explained in Section III-A.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these documents may come from various domains, such as healthcare, science, chemistry, law, safety, and finance. Consequently, creating annotated corpora or labeled data for these human-generated documents is highly resource-intensive and time-consuming as it requires many rules to be generated for IE task purposes [16], [34], [171].…”
Section: ) Challenges Based On Rq3: Issues Related To Future Applicat...mentioning
confidence: 99%
“…A FDNN can be comprised by a broad category of DNNs and fuzzy inference systems in different architectures. Current architectures in the literature can be classified into three categories: sequential FDNN, parallel FDNN, and cooperative FDNN [ 189 ].…”
Section: Deep Learning Models and Methodsmentioning
confidence: 99%
“…Although it is difficult to collect evidence to support IoT and Cloud Computing cybercrime cases without deductive knowledge, and even more challenging to connect various pieces of evidence into a chain of custody, it is critically important to consider the classification of the crime, the methods of collecting evidence, and all relevant laws and regulations in an extremely consistent manner use of blockchain technology [20]. The systematic classification of data, using advanced data mining techniques to categorize data [21], to aid in a more accurate analysis should be the norm. Such classifications should also assist analysts to predict the target class for each new case in the data and information flow.…”
Section: When One Takes Into Account Assessing Iot and Cloudmentioning
confidence: 99%